Strategy to Increase Customer Loyalty Through A Multisensory Approach at A Five-Star Hotel in Surabaya - Trinindya Eksact Daruni; Jiwangga Hadi Nata; Dian Yulie Reindrawati; Mohammad Nurul Huda; Nur Emma Suriani (TIJAB (The International Journal of Applied Business), 2026)
Background: The hospitality industry is highly competitive and continuously seeks strategies to attract and retain customers. Multisensory marketing, which engages all five senses, has emerged as an effective way to enrich the guest experience and to foster loyalty. Objective: This study examines how multisensory strategies influence customer loyalty at a five-star hotel in Surabaya, focusing on key loyalty metrics, including repeat visits, willingness to recommend, and emotional attachment. Method: A qualitative approach was employed through in-depth interviews with hotel staff and real guest participants. Data were coded using a structured thematic framework, with illustrative raw excerpts included to ensure transparency. Ethical approval was obtained, and informed consent was secured from all participants. Results: The findings reveal that the hotel's multisensory applications—including visual ambiance, signature scents, curated soundscapes, and diverse culinary experiences—enhance customer satisfaction and contribute to loyalty patterns. Visualized results as presented in the thematic tables and charts, highlight the key links between sensory engagement and loyalty behaviors. Conclusion: Multisensory strategies effectively create memorable, emotionally engaging guest experiences, strengthening loyalty by increasing satisfaction, repeat patronage, and advocacy. These findings underscore the value of integrating multisensory marketing as a sustainable competitive advantage in luxury hospitality. Keywords: Customer Loyalty; Multisensory Marketing; Hospitality Strategy; Guest Experience; Sensory Branding; Emotional Engagement.